2019
DOI: 10.1021/acs.jpclett.9b00018
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally Resolved Ultrafast Exciton Transfer in Mixed Perovskite Quantum Wells

Abstract: Solution-processed perovskite quantum wells have been used to fabricate increasingly efficient and stable optoelectronic devices. Little is known about the dynamics of photogenerated excitons in perovskite quantum wells within the first few hundred femtosecondsa crucial time scale on which energy and charge transfer processes may compete. Here we use ultrafast transient absorption and two-dimensional electronic spectroscopy to clarify the movement of excitons and charges in reduced-dimensional perovskite soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
125
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(141 citation statements)
references
References 50 publications
10
125
0
Order By: Relevance
“…For P2 film, the strongest GSB was located at 396 nm (n 1 domain) with ultralong bleaching delay of 78 ps (Figure S7, Supporting Information). It has been confirmed that excitation relaxation and exciton transfer in 2D perovskite films occur within initial stages (i.e., from ≈0.1 to ≈10 ps) while emission occurs after 10s ps . However, we did not found any steady PL signal from n 1 domain (Figure S8, Supporting Information).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…For P2 film, the strongest GSB was located at 396 nm (n 1 domain) with ultralong bleaching delay of 78 ps (Figure S7, Supporting Information). It has been confirmed that excitation relaxation and exciton transfer in 2D perovskite films occur within initial stages (i.e., from ≈0.1 to ≈10 ps) while emission occurs after 10s ps . However, we did not found any steady PL signal from n 1 domain (Figure S8, Supporting Information).…”
supporting
confidence: 54%
“…Domain distribution and formation dynamics in quasi‐2D perovskite films are demonstrated highly sensitive to spacer cations . Remarkably, a mixed spacer system was set up to significantly modulate the component of quasi‐2D perovskite films .…”
mentioning
confidence: 99%
“…The evolutions of the peak and FWHM illustrate the continuous competition of bleach signals from different n value domains. In stage II, an ultrafast exciton transfer from small-n domains (n ≤ 3) to large-n domains (n ≥ 4) occurs in the time span of 0.7-1.3 ps 39,40,50,51 , resulting in a fast redshift of the broadened bleach peak. In stage III, excitons begin to dissociate into free charge carriers and charge transfer occurs subsequently within a few picoseconds [51][52][53][54][55] , which induces a further redshift of the bleach peak.…”
Section: Fabrication and Structural Analysis Of Cspbclbr 2 Nanocrystalmentioning
confidence: 99%
“…phases of different n) using time resolved spectroscopy. 13,33 This downhill energy transfer process is of particular relevance in hybrid 2D-3D perovskite solar cells, where phases of distinct n co-exist. 15 The transfer between perovskite layers of identical thickness, however, has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%